The public health impact of recombinant herpes zoster vaccination in adults over 50 years in Spain - Andrea García; Laura Amanda Vallejo-Aparicio; Rosario Cambronero Martinez (Human Vaccines & Immunotherapeutics)
The recombinant zoster vaccine (RZV) is included in the Spanish National Immunisation Programme for adults 65 years of age (years), with a potential progressive catch-up program for adults 66–80 years, starting with 80 years. However, the risk of herpes zoster (HZ) increases significantly from 50 years. We estimated the public health impact (PHI) of vaccinating adults ≥50 years in Spain versus no vaccination, using a Markov model adapted to the Spanish setting. The model simulated a hypothetical ≥50 years cohort over a lifetime, with inputs from Spanish publications, databases, or publications from other countries where Spanish data were unavailable. Base case inputs included 67.7% RZV coverage and 61.1% second dose compliance. Outputs included clinical outcomes avoided, healthcare resource use avoided, and number-needed-to-vaccinate (NNV) to prevent one HZ case. Deterministic (DSA) and probabilistic sensitivity analyses (PSA) were also conducted. The model estimated that, compared with no vaccination, vaccinating adults ≥50 years in Spain (N = 19,850,213) with RZV could prevent 1,533,353 HZ cases, 261,610 postherpetic neuralgia episodes, 274,159 other complications, and 138 deaths through the cohorts’ remaining lifetime, mostly in the 50–59 years cohort. Furthermore, 3,500,492 primary care visits and 71,156 hospitalizations could be avoided, with NNV = 9 to prevent one HZ case. DSA predicted NNV = 7 to prevent one HZ case when second dose compliance was increased to 100%. PSA demonstrated ≥200,000 and ≥1,400,000 cases could be prevented in 86.9% and 18.4% of simulations, respectively. Starting RZV from 50 years could therefore prevent a substantial number of HZ cases and complications. Increasing RZV coverage and second dose compliance could further alleviate PHI of HZ.